Pharmacological Agent GW4869 Inhibits Tick-Borne Langat Virus Replication to Affect Extracellular Vesicles Secretion - Md Bayzid; Biswajit Bhowmick; Waqas Ahmed; Girish Neelakanta; Hameeda Sultana (Viruses, 2025)
GW4869, a cell-permeable, selective inhibitor of neutral sphingomyelinase is a pharmacological agent that blocks the production and release of extracellular vesicles (EVs). Our previous studies have shown that GW4869 inhibits flaviviral loads in tick, mosquito and mammalian cells, including murine cortical neurons. Yet the mechanism(s) of GW4869 inhibitor upon viral infections were not addressed. In the current study, we focused on how GW4869 interferes with Langat Virus (LGTV, a tick-borne flavivirus) replication in ISE6 tick cells. First, we found that GW4869 is neither cytotoxic at tested doses of 50, 100, and 150 µM in tick cells, nor does it directly bind to the free LGTV present in cell culture supernatants. When tick cells were treated with GW4869, followed by infection with viral stock at dilutions of 10−2, 10−3, 10−4 (the infectious dose determination by viral dilution assay), it affected LGTV replication in tick cells. A reduction in viral burden was noted in GW4869-treated tick cells, which constituted more than half the amount of decrease when compared to the mock control. Next, GW4869 treatment not only resulted in decreased LGTV transcript levels in tick cells and EVs derived from these infected cells, but also revealed diminished EVs concentrations. Enhanced IsSMase transcripts in the LGTV-infected group was noted upon GW4869 treatment, thus suggesting a host response to perhaps inhibit virus replication. In addition, GW4869 treatment reduced LGTV loads in density gradient EVs fractions, which correlated with decreased EVs concentration in those fractions. These data not only indicate that GW4869 affects LGTV replication, but that it also interferes with EV secretion and release from tick cells. Lastly, we found that GW4869 inhibits LGTV replication in tick cells but does not directly affect the infectivity of LGTV viral particles. Overall, our study suggests that GW4869 is a potential therapeutic inhibitor in controlling tick-borne diseases.